UPAYA GURU BIMBINGAN KONSELING DALAM MENANGGULANGI KECEMASAN SISWA SAAT BERBICARA DI DEPAN UMUM DENGAN TEKNIK RELAKSASI SMP NEGERI 6 PERCUT SEI TUAN - Mila Agustina; Saiful Akhyar Lubis (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Research on Teacher Counseling Efforts in Tackling Student Anxiety whenSpeaking in Public with Relaxation Techniques at SMP Negeri 6 Percut Sei Tuan Academic Year 2019. Aims to find out and describe the handling by using appropriate relaxation techniques and should be given to students in dealing with student anxiety when public speaking, with the limitation of the formulation of the problem namely to know the efforts of counseling guidance teachers in tackling student anxiety when speaking in public with relaxation techniques of SMP Negeri 6 Percut Sei Tuan Academic Year 2019. This research is a descriptive qualitative research. The research subjects were 2 (two) guidance and counseling teachers and 6 (six) students. While the object of his research is relaxation techniques in dealing with student anxiety when speaking in public at Percut Sei Tuan Middle School. The method of data collection is done through observation, interviews, documentation. The results showed that relaxation techniques can overcome student anxiety when speaking in public.Keywords: Speaking Anxiety, Relaxation Techniques